A GMC Oxidoreductase GmcA Is Required for Symbiotic Nitrogen Fixation in Rhizobium leguminosarum bv. viciae - Zou, Qian; Luo, Sha; Wu, Hetao; He, Donglan; Li, Xiaohua; Cheng, Guojun (Frontiers in Microbiology, 2020)
GmcA is a FAD-containing enzyme belonging to the GMC (glucose-methanol-choline oxidase) family of oxidoreductases. A mutation in the R. leguminosarum gmcA gene was generated by homologous recombination. The mutation in gmcA did not affect the growth of R. leguminosarum, but it displayed decreased antioxidative capacity at H2O2 conditions higher than 5 mM. The gmcA mutant strain displayed no difference of glutathione reductase activity, but significantly lower level of the glutathione peroxidase activity than the wild type. Although the gmcA mutant was able to induce the formation of nodules, the symbiotic ability was severely impaired, which led to an abnormal nodulation phenotype coupled to a 30% reduction in the nitrogen fixation capacity. The observation on ultrastructure of 4-week pea nodules showed that the mutant bacteroids tended to start senescence earlier, and accumulate poly-β-hydroxybutyrate (PHB) granules. In addition, the gmcA mutant was severely impaired in rhizosphere colonization. Real-time quantitative PCR showed that the gmcA gene expression was significantly upregulated in all the detected stages of nodule development, and statistically significant decreases in the expression of the redoxin genes katG, katE and ohrB, were found in gmcA mutant bacteroids. LC-MS/MS analysis quantitative proteomics techniques were employed to compare differential gmcA mutant root bacteroids in response to the wild type infection. Sixty differentially expressed proteins were identified including 33 up-regulated and 27 down-regulated proteins. By sorting the identified proteins according to metabolic function, fifteen proteins were transporter protein, twelve proteins were related to stress response and virulence, and nine proteins were related to transcription factor activity. Moreover, nine proteins related to amino acid metabolism were over-expressed.